Safety characterisation and inhibition of fungi and bacteria by a novel multiple enterocin-producing Enterococcus lactis 4CP3 strain. (May 2018) - Ben Braïek, Olfa; Cremonesi, Paola; Morandi, Stefano; Smaoui, Slim; Hani, Khaled; Ghrairi, Taoufik
Abstract: This study aims to characterise a potential bacteriocinogenic lactic acid bacterial strain isolated from a raw pink shrimp ( Palaemon serratus ) and evaluate its safety aspect. The strain designated as 4CP3 was noted to display antibacterial activities ( P < 0.05) against Gram-positive and Gram-negative foodborne pathogens ( Listeria monocytogenes and Pseudomonas aeruginosa ) and some filamentous fungi (e.g. Aspergillus niger A79). Phenotypic and molecular techniques as well as phylogenetic analysis identified the isolate 4CP3 as Enterococcus lactis . Its produced antimicrobial substance was determined as a bacteriocin that was stable over a wide range of pH (2–10) and after heating at 100 °C for 15 min. The maximum bacteriocin production was 1400 AU/ml recorded after 12 h of incubation in de Man, Rogosa and Sharpe (MRS) broth medium at 30 °C. The mode of action of the bacteriocin produced by 4CP3 strain was identified as bactericidal against L. monocytogenes EGDe 107776 and P. aeruginosa ATCC 27853. By specific PCR amplifications, E. lactis 4CP3 was shown to produce the enterocins A, B and P. To our knowledge, this feature is newly described for E. lactis strain isolated from raw shrimps. Regarding safety aspect of E. lactis 4CP3, it has been demonstrated that this strain was not haemolytic, gelatinase negative, sensitive to vancomycin, and free of common antibiotic resistance genes and virulence factors. Therefore, it may be useful as a safe natural agent in preservation of foods or as a new probiotic strain in food and feed. Highlights: 4CP3 strain was isolated from raw pink shrimp " Palaemon serratus ". 4CP3 strain is a multiple enterocin-producing (A, B and P) Enterococcus lactis . 4CP3 strain displays antimicrobial and antifungal activities. E. lactis 4CP3 exhibits bactericidal mode of action against foodborne bacteria. Safety aspect of E. lactis 4CP3 strain was assessed by diverse tests.